Analisa ANALISA STUDI BANDING HOTEL NEO PALANGKA RAYA - Kurniawan, Chantika Dian Mentari; Hamidah, Noor (JURNAL PERSPEKTIF ARSITEKTUR, 2023)
Hotel is a building in the form of accommodation that uses part or all of the building to provide services such as lodging, provision of food and drinks, as well as several other services for commercial needs for the general public. Hotel Neo as one of the popular hotels in Palangka Raya is one of the hotels that can be emulated or used as a reference in a design study. The research method used qualitative method. In this study is the observation step in which the results of this study are in the form of descriptive explanations regarding the data obtained from the field so that the superiority of the design can be seen.